Pengaruh Kualitas Produk dan Pengendalian Internal Terhadap Kepuasan Konsumen E-Commerce - Silvia Gunawan; Candra Sinuraya (Universitas Kristen Maranatha, 2022)
Consumer satisfaction is an important aspect that needs to be considered by e-commerce sellers. Good product quality and supported by proper internal control will increase e-commerce customer satisfaction. This study aims to examine the effect of product quality and internal control partially on e-commerce consumer satisfaction. The sample of this research is active undergraduate students at various universities spread across various regions who use e-commerce by using a sampling technique in the form of purposive sampling. Data was collected by means of a survey in the form of a questionnaire. The sample obtained was 100 respondents. The data analysis technique used is multiple linear regression. The results of the t-test indicate that product quality has a positive effect on e-commerce consumer satisfaction, meaning that consumers perceive the product received has good quality because the product received is in accordance with the order without any damaged products. In addition, internal control also has a positive effect on e-commerce consumer satisfaction, meaning that e-commerce sellers have provided protection for products purchased by consumers so that consumer satisfaction increases. Keywords: Product Quality, Internal Control, Consumer Satisfaction, and E-commerce